2013
DOI: 10.1177/0748730413494561
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Circadian Disruption Elevates the IL-6 Response to Lipopolysaccharide in Blood

Abstract: The immune system is regulated by circadian clocks within the brain and immune cells. Environmental circadian disruption (ECD), consisting of a 6-h phase advance of the light:dark cycle once a week for 4 weeks, elevates the inflammatory response to lipopolysaccharide (LPS) both in vivo and in vitro. This indicates that circadian disruption adversely affects immune function; however, it remains unclear how the circadian system regulates this response under ECD conditions. Here, we develop an assay using ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 19 publications
4
44
1
1
Order By: Relevance
“…The intensity of cytokine production upon stimulation appears to sustain rhythmicity in constant darkness, conversely, circadian differences in survival in response to LPS could not be observed under these conditions . It should be noted that the majority of studies investigating diurnal rhythms in susceptibility to infection were consistent regarding the trough in survival rate during the late rest phase despite the use of different protocols ranging from TNF and LPS in BALB/c mice to coxsackie B3 virus infection in CD‐1 mice .…”
Section: Daily Oscillations In Immunitymentioning
confidence: 99%
“…The intensity of cytokine production upon stimulation appears to sustain rhythmicity in constant darkness, conversely, circadian differences in survival in response to LPS could not be observed under these conditions . It should be noted that the majority of studies investigating diurnal rhythms in susceptibility to infection were consistent regarding the trough in survival rate during the late rest phase despite the use of different protocols ranging from TNF and LPS in BALB/c mice to coxsackie B3 virus infection in CD‐1 mice .…”
Section: Daily Oscillations In Immunitymentioning
confidence: 99%
“…Further, this could lead to potential novel therapeutic options and changes in therapeutic application (e.g., chronotherapy [Bellamy et al, ; Bruguerolle & Labrecque, ; Buttgereit, Smolen, Coogan, & Cajochen, ; Gilron, ; Sunil, Srikanth, Rao, & Murthy, ]). An examination of the contribution of the immune system to inflammatory pain found that a disruption of the circadian cycle (as is possible under disease conditions) causes an increase in the secretion of the proinflammatory cytokines and consequently an enhancement of proinflammatory immune responses (Adams, Castanon‐Cervantes, Evans, & Davidson, ). IL‐6, a cytokine with both pro‐ and anti‐inflammatory actions, has been documented as having a robust circadian rhythm in patients with RA, with elevated levels in the morning (Arvidson et al, ; Perry, Kirwan, Jessop, & Hunt, ).…”
Section: Circadian Rhythms Neuroinflammation and Painmentioning
confidence: 99%
“…Exposure to light at night and to non-24-h light cycles alters inflammatory responses in the peripheral and central nervous systems (113)(114)(115). Environmental circadian disruption is similarly associated with changes in immune response (116)(117)(118). In humans, even acute circadian misalignment reduces circulating cortisol levels and increases inflammatory cytokines (61), and shift work is associated with increased risk for several inflammatory pathologies (119).…”
Section: Inflammatory Disorders and Cancermentioning
confidence: 99%